2022
DOI: 10.1186/s13045-022-01337-w
|View full text |Cite
|
Sign up to set email alerts
|

Connecting telomere maintenance and regulation to the developmental origin and differentiation states of neuroblastoma tumor cells

Abstract: A cardinal feature that distinguishes clinically high-risk neuroblastoma from low-risk tumors is telomere maintenance. Specifically, neuroblastoma tumors with either active telomerase or alternative lengthening of telomeres exhibit aggressive growth characteristics that lead to poor outcomes, whereas tumors without telomere maintenance can be managed with observation or minimal treatment. Even though the need for cancer cells to maintain telomere DNA—in order to sustain cell proliferation—is well established, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 137 publications
1
5
0
Order By: Relevance
“…The phenotypic characteristics of these two cell populations are largely determined by the activation of specific transcriptional circuitries: while ADRN cells express markers of sympatho-adrenergic differentiation, MES cells appear undifferentiated and more similar to their neural crest progenitors ( 7 , 8 ). Interestingly, the ADRN and MES classification coincides with the characteristics previously described for N/I-type and S-type cells, respectively ( 10 ).…”
Section: Introductionsupporting
confidence: 84%
“…The phenotypic characteristics of these two cell populations are largely determined by the activation of specific transcriptional circuitries: while ADRN cells express markers of sympatho-adrenergic differentiation, MES cells appear undifferentiated and more similar to their neural crest progenitors ( 7 , 8 ). Interestingly, the ADRN and MES classification coincides with the characteristics previously described for N/I-type and S-type cells, respectively ( 10 ).…”
Section: Introductionsupporting
confidence: 84%
“…Firstly, due to a lack of individual-level records, we could not obtain specific treatment details of the patients, including the surgical techniques and chemotherapy or radiotherapy plans adopted, which restricted our further evaluation of their impact on the long-term survival of the patients. Secondly, recent studies have shown that specific molecular characteristics of neuroblastoma are associated with tumor sub-categories [38,39] and clinical outcomes [34,40]. Although we applied stratification factors to reduce data bias, cytogenetic, molecular, or unknown factors related to patients' survival were still unavoidably omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of TMM correlates with more frequent relapse in patients with high-risk neuroblastoma, with the majority of relapse cases also exhibiting activation of TMMs [ 110 ]. Conversely, there is a clear association between low-risk neuroblastoma, which often undergoes spontaneous tumor regression, and the absence of TLM activation [ 111 ]. It is speculated that spontaneous regression in low-risk neuroblastoma takes place when telomere reserves are exhausted due to the lack of TMM and the inability to counteract telomere shortening pathways [ 111 ].…”
Section: Long Non-coding Rnas In Neuroblastomamentioning
confidence: 99%
“…Conversely, there is a clear association between low-risk neuroblastoma, which often undergoes spontaneous tumor regression, and the absence of TLM activation [ 111 ]. It is speculated that spontaneous regression in low-risk neuroblastoma takes place when telomere reserves are exhausted due to the lack of TMM and the inability to counteract telomere shortening pathways [ 111 ]. These findings underscore the potential prognostic and therapeutic significance of TMMs in neuroblastoma.…”
Section: Long Non-coding Rnas In Neuroblastomamentioning
confidence: 99%